Improving the Teaching of Arabic Language Through Effective Use of YouTube Video As Audio-Visual Aids - Abdullahi Shehu Onisabi; Salih M. Jum’ah Alaso (IJUS | International Journal of Umranic Studies, 2022)
This study examines ways of improving the teaching and learning of Arabic language through the application of YouTube video clips as audio-visual aids. This becomes imperative as Arabic is not just a language of religion used by Muslims world over in their religious activities, but as a language spoken by millions of people in the world. It is the official language of the South West Asian and most of the North African countries. It is the 5th in the World’s 10 most influential languages and one of the official languages of many international organizations. The study was carried out by selecting 18 students of Arabic language in Kaduna State College of Education, Gidan –Waya and Kwara State University, Malete to constitute sample of the study. Descriptive method was adopted and Pre-test and Post – test was conducted. Data were collected through the essay writing, translation and structure test. The data were analyzed through the descriptive statistics of frequency (f) and percentage (%). The findings, based on the result of the tests, revealed that the subjects performed better and they were able to demonstrate higher linguistic communicative competence in Arabic language. Finally, the study recommends that YouTube videos should be integrated into Arabic instruction delivery strategies.